2018
DOI: 10.1037/dev0000503
|View full text |Cite
|
Sign up to set email alerts
|

Night awakening in infancy: Developmental stability and longitudinal associations with psychomotor development.

Abstract: Fragmented sleep is common in infancy. Although night awakening is known to decrease with age, in some infants night awakening is more persistent and continues into older ages. However, the influence of fragmented sleep on development is poorly known. In the present study, the longitudinal relationship between fragmented sleep and psychomotor development (Bayley Scales of Infant and Toddler Development [Bayley-III]; Bayley, 2009) was investigated in infants with (≥3 night awakenings, n = 81) and without fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
(84 reference statements)
2
17
1
Order By: Relevance
“…Therefore, night awakenings are a normative feature for children under one year of age. This is supported by recent studies in which the number of night awakenings and staying awake at night (<age 1 yr) were not associated with adverse developmental consequences (Mäkelä et al 2018;Pennestri et al, 2018). However, during the second year, the average number of night-awakenings decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, night awakenings are a normative feature for children under one year of age. This is supported by recent studies in which the number of night awakenings and staying awake at night (<age 1 yr) were not associated with adverse developmental consequences (Mäkelä et al 2018;Pennestri et al, 2018). However, during the second year, the average number of night-awakenings decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
“…The eye-tracking data of the Switch task were saved as text files and analyzed with gazeAnaly-sisLib, a library of Matlab routines for gaze data analysis (Lepp€ anen, Forssman, Kaatiala, Yrttiaho, & Wass, 2015). The areas of interest were manually defined, and these areas covered the central area of the screen, the rectangle where the monkey appeared, and the area between the center and the rectangle.…”
Section: Eye-tracking Analysis At 24 Monthsmentioning
confidence: 99%
“…The average numbers of scorable trials in the pre and postswitch blocks were 4.3 and 3.9, respectively, with no difference between the blocks (t(236) = 1.477, p = .141). The correlations between video-based (i.e., manually coded) and eye-tracking data from children saccadic response tasks have been shown to be very high (Lepp€ anen et al, 2015).…”
Section: Eye-tracking Analysis At 24 Monthsmentioning
confidence: 99%
“…However, these studies have yielded mixed findings. Whereas some studies did not observe correlations between different aspects of sleep and overall cognitive functioning (Mäkelä et al, ; Mindell & Lee, ; Spruyt et al, ), other studies have yielded divergent patterns of results. For example, one study on a small sample of low‐risk infants found that more motor activity in sleep and more fragmented sleep were associated with lower mental developmental index (MDI) scores at 10 months (Scher, ).…”
Section: Introductionmentioning
confidence: 98%
“…However, links between infant sleep and cognitive functioning are less well understood. Several studies (e.g., Mäkelä et al, ; Scher, ) have examined the relations between various aspects of sleep and performance on the Bayley Scales of Infant Development (Bayley, , ), a standardized assessment that captures infant functioning across multiple cognitive domains (e.g., sensorimotor development, exploration and manipulation, memory). Other studies have relied on maternal report measures of infants’ cognitive functioning (e.g., Mindell & Lee, ).…”
Section: Introductionmentioning
confidence: 99%